Five species under Dicranomyia (Dicranomyia) mitis (Meigen, 1830) (Diptera, Limoniidae) - Starý, Jaroslav; Stubbs, Alan E. (Zootaxa, 2015)
Five species previously usually treated as Dicranomyia (Dicranomyia) mitis (Meigen, 1830) are redescribed and named with already existing names, viz. D. (D.) mitis [s. str.], D. (D.) affinis (Schummel, 1829), D. (D.) quadra (Meigen, 1838), sp. restit., D. (D.) lutea (Meigen, 1804), and D. (D.) imbecilla Lackschewitz in Lackschewitz & Pagast, 1941, stat. n. All important characters of the wing, male tarsi and male and female terminalia are illustrated. A key to D. (D.) mitis and allies is appended.